The effects of feedback valence and style on need satisfaction, self-talk, and perseverance among tennis players: An experimental study - De Muynck, G. J.; Vansteenkiste, M.; Delrue, J.; Aelterman, N.; Haerens, L.; Soenens, B. (Journal of Sport & Exercise Psychology, 2017)
Grounded in self-determination theory, this experimental study examined whether the valence (i.e., positive vs. negative) and style (i.e., autonomy-supportive vs. controlling) of normative feedback impact the self-talk, motivational experiences (i.e., psychological need satisfaction and enjoyment), and behavioral functioning (i.e., perseverance and performance) of tennis players (N=120; Mage=24.50±9.86 years). Positive feedback and an autonomy-supportive style positively influenced players` enjoyment and perseverance, with psychological need satisfaction and self-talk playing an intervening role. While positive feedback yielded its beneficial effect via greater competence satisfaction and decreased negative self-talk, the beneficial impact of an autonomy-supportive communication style was explained via greater autonomy satisfaction.